Application of Family Function in Dealing with Fujoshi and Fudanshi Teenagers in Bandar Selamat Village - Sudirman Sudirman; Adinda Yulfina Nasution; Rosramadhana Rosramadhana (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2022)
Teenagers as fans of homosexual love stories are considered as a form of deviation that occurs. Teenagers' hobbies violate religious and social values in society. Teenagers like things that are considered deviant. As a result, there is a change in adolescent behavior, adolescents become closed, addicted to homosexual content, apathetic and emotional. The purpose of this study was to describe the existence of fujoshi and fudanshi adolescents based on their characteristics (self-closing, addiction, apathy, and emotionality) and to determine the application of family functions in tackling the character of fujoshi and fudanshi adolescents in Bandar Selamat Village. This research was conducted using a descriptive research method with a qualitative approach. Data collection in this qualitative research uses interactive techniques including participant observation, interviews, and documentation. The data analysis technique is done by reducing the data, displaying the data and drawing conclusions. The validity of this research uses credibility, dependability, and confirmability tests. The results showed a description of the existence of fujoshi and fudanshi teenagers based on their characteristics. Fujoshi and fudanshi teenagers who consume homosexual stories can be overcome by implementing family functions. The application of family functions in dealing with fujoshi adolescents includes the application of the functions of religion, love, protection, reproduction as well as socialization and education. The five functions implemented by parents can overcome the behavior of children who are fans of homosexual love stories. For this reason, as parents, they should be able to balance themselves with technological developments today so that they can monitor all children's activities on social media.